Culture and conflict : nation-building in Denmark and Scandinavia, 1800-1930 - Krogh, Sine; Mednick, Thor J.; Lykke Grand, Karina (Aarhus University Press, 2022)
"Cultural differences are often the trigger for conflict - whether politically motivated or arising from dissonant understandings of national culture. But what we regard as distinctive today in our cultural heritage or day-to-day cultural experience is deeply rooted in the rich diversity of the national currents of the nineteenth century. Culture and Conflict: Nation-building in Denmark and Scandinavia, 1800-1930 explores the many strands of Danish and Scandinavian culture that helped to shape these cultural identities. The sixteen contributions in this volume analyse how competing national agendas influenced the development of political life as well as literature, the visual arts, and music. A central theme is the cultural conflicts that formed an essential part of nineteenth-century nation-building. Culturally as well as politically, boundaries were drawn up, ideologies were formulated and discussed, and determined attempts were made to suppress divergent cultural voices in the drive to forge strong national or Scandinavian narratives. The result of these conflicts was the enduring cultural struggles and culture wars that form the subject of this volume. The contributions, by scholars from Denmark, Britain, Norway, the United States, and Germany, bring a broad and interdisciplinary perspective to bear on these distinctively Nordic themes. Aimed both at students and at established scholars, the chapters discuss the many facets of nationalism, its cultures, and its countercultures, as well as revisiting the historiography of the 1800-1930 period with a more pluralistic approach."--Back cover.